The National Defense Education as Students’ Character Education - Yunita Yunita; Nastiti Mufidah (International Journal of Education and Humanities, 2022)
Global society is entering a new stage of development called the Fourth Industrial Revolution (Industry 4.0). The rapid and massive development of digital technology has pushed the world into a new industrial order. The new industrial order presents opportunities as well as challenges for young generation. Character education, a value education involving knowledge (cognitive aspect), feeling, and action, is projected to be able to prepare young generation to face Industry 4.0. The purpose of this study was to describe the implementation of National Defense Education as a medium for developing student character at Siliwangi University (UNSIL) specially defending the state value. This is qualitative research using a case study design. The research subjects in this study were the parties involved in the National Defense Education held by Siliwangi University. The research results suggest that the National Defense Education was a tentative semi-military education. This activity is generally aimed at character building, especially to build students’ awareness of the nation, discipline, kinship, and independence.